Influence of variable salinity and low light on copper accumulation in the potential seagrass bioindicator, Zostera muelleri. (November 2020) - Skillington, A.; Flint, N.; Anastasi, A.; Dwane, G.; Jackson, E.L.
Abstract: Utilising a potential coastal trace element bioindicator requires understanding its accumulation patterns under varying environmental scenarios. The present study aimed to understand, from two experiments, the influence and effect of low light (15.3 μmol photons m −2 s −1 ) and variable salinity (normal 36 and reduced 29) on Zostera muelleri accumulating variable Cu concentrations (control, low 5 μg L −1 and high 50 μg L −1 ) in order to determine its capability as a potential trace element bioindicator. Initial (24 h) leaf Cu concentration was in proportion to exposure Cu concentrations, irrespective of manipulated environmental conditions, suggesting passive accumulation. Final below-ground Cu concentrations, during the low light experiment, significantly increased over time, suggesting active Cu accumulation. Zostera muelleri leaves could act as a Cu bioindicator at times of reduced light and salinity while further interpretation is required of below-ground Cu concentrations. It is recommended that Z . muelleri could be utilised as a Cu bioindicator. Highlights: Variable environmental variables (salinity or low-light) did not influence initial leaf copper accumulation. Leaf copper accumulation, from a one time dosage, was in proportion to exposure levels. Final leaf copper concentrations either decreased or increased due to biomass dilution or potential new growth. Below-ground copper concentrations increased from downwards translocation or overtime due to active copper accumulation.